Synthesis and Characterization of Process-Related Impurities of Antihypertensive Drug Olmesartan Medoxomil - G. Venkanna; G. Madhusudhan; K. Mukkanti; A. Sankar; Y. Sampath Kumar; G. Venakata Narayana (Journal of Chemistry)
Olmesartan medoxomil (1) is the latest angiotensin receptor antagonist approved by the FDA for the treatment of hypertension. During the process development of olmesartan medoxomil, three process-related impurities were observed along with the final API. These impurities were identified as isopropyl olmesartan (12), dimedoxomil olmesartan (19), dibiphenyl olmesartan (17). The present work describes the synthesis and characterization of all these three impurities.